Current status of perimesencephalic non-aneurysmal subarachnoid hemorrhage - Hou, Kun; Yu, Jinlu (Frontiers in Neurology, 2022)
Perimesencephalic nonaneurysmal subarachnoid hemorrhage (PNSAH) is a distinctive disease, representing SAH centered in perimesencephalic cisterns, with negative angiography findings. In recent years, the number of patients with PNSAH has increased significantly; however, the knowledge of PNSAH is insufficient. Therefore, we performed a review of the literature from a PubMed search and recounted our understanding of PNSAH. In this review, we summarized that current high-resolution computed tomography angiography can be accepted as a replacement for digital subtraction angiography (DSA) to rule out aneurysms in PNSAH with strict criteria, and repeated DSA may not add further diagnostic value. The current hypothesis about the etiology of PNSAH is that there is deep vein rupture from aberrant venous anatomy and increased intracranial venous pressure. PNSAH is associated with mild symptoms and with a lower rate of hydrocephalus and symptomatic vasospasm. For PNSAH, the conservative treatment has been mainstream. Surgical intervention is uncommon. PNSAH has a benign clinical course and an excellent prognosis; in long-term follow-up, death was rare. This information is very important.